The Role of Teachers in Shaping Student Character after the Covid-19 Pandemic - Siregar, Royhanun; Novianti, Williya; Annisa, Dona Fitri; Alawiyah, Tuti (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2024)
The study aims to determine the role of teachers in shaping student character after the co-19 pandemic through civic education learning in class IV of SD Negeri 200217 Padangsidimpuan. The type of research is descriptive qualitative. The informants in this study were the principal as the key informant and the fourth grade teacher as the main informant. Data collection techniques used: 1) observation, and 2) interview. Based on the results of the study, it is concluded that the role of homeroom teacher IV as a teacher at SD Negeri 200217 Padangsidimpuan in shaping student character through civic education learning has been done as much as possible by making learning objectives, presenting material, making learning activities, and rules based on student character building. This can be seen from the existence of character lesson plans and syllabus, teachers who describe the values contained in the material, create active and efficient learning activities with the application of new methods and ideas, and the existence of regulations that have implications for educated values. Teachers have also modelled and practised good behaviour with students inside and outside the classroom. This shows that teachers play a role as teachers in shaping student character after the co-19 pandemic through civic education learning.